KETERLAMBATAN LAPORAN AUDIT : LEVERAGE, PROFITABILITAS, DAN UMUR PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Lestari; Deni Rustandi (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
The timeliness of audit report issuance is a critical aspect of financial reporting, as it relates to the relevance of information for investors and the efficiency of the capital market. This study aims to analyze the effects of leverage, profitability, and firm age on audit report lag, with firm size as a moderating variable, among non-essential consumer goods companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This study employs a quantitative approach with a causal design and utilizes secondary data obtained from the financial statements of public companies. The research sample was selected using purposive sampling, comprising a total of 111 company observations. The analysis method employed was Moderated Regression Analysis (MRA) using EViews 13 software. The results of the study indicate that leverage has a negative and significant effect on audit report lag, while profitability and firm age do not have a significant effect on audit report lag. Furthermore, firm size has a positive and significant effect on audit report lag, but it does not moderate the relationship between leverage, profitability, and firm age and audit report lag. This study makes an empirical contribution by incorporating firm size as a moderating variable in the model analyzing audit report lags in the non-essential consumer goods sector, thereby enriching the literature on the determinants of audit report lags in the Indonesian capital market.